Prevalence of the primary LHON mutations in Northern Finland associated with bilateral optic atrophy and tobacco‐alcohol amblyopia. (12th September 2012) - Korkiamäki, Paula; Kervinen, Marko; Karjalainen, Karoliina; Majamaa, Kari; Uusimaa, Johanna; Remes, Anne M.
Abstract. Purpose: Leber hereditary optic neuropathy (LHON) is regarded as the most common mitochondrial disease. We have previously reported comprehensive population‐based epidemiological data on common mitochondrial DNA (mtDNA) mutations including m.3243A>G, m.8344A>G and large‐scale mtDNA deletions in Northern Finland. Our aim was to investigate the prevalence of primary LHON mutations and mutations in the four mtDNA genes considered hot spots for LHON in the same population. Methods: The study population consisted of 42 adult patients with an aetiologically undefined bilateral optic atrophy. The major LHON mutations m.3460G>A, m.11778G>A and m.14484T>C were analysed by restriction fragment length polymorphism (RFLP), and MTND1, MTND6 and MTATP6 genes were sequenced. MTND5 gene was analysed by conformation‐sensitive gel electrophoresis (CSGE). Results: No major LHON mutations were found in the population of the province of Northern Ostrobothnia giving the prevalence of these mutations 0–1.36:100 000 (95% CI). However, two main mutations were found elsewhere in Northern Finland, homoplasmic m.11778G>A from Kainuu and heteroplasmic m.3460G>A from Central Ostrobothnia. Furthermore, tobacco‐alcohol amblyopia was diagnosed in five patients in the study population and one of them had m.11778G>A. Conclusion: The prevalence of the three major LHON mutations is lower in Northern Finland than elsewhere in Finland or in Western Europe. As LHON and tobacco‐alcohol amblyopia have a similar phenotype, we recommend analysing the known LHON‐associated mutations before setting tobacco‐alcohol amblyopia diagnosis.